THE TREASURE ARTS AND ISLAMIC CULTURES: MOSQUES’ ARCHITECTURES AND CALLIGRAPHIES IN ARCHIPELAGO - Toipah, Toipah (Teosofia: Indonesian Journal of Islamic Mysticism, 2020)
This article discusses about architectures and ornaments in the mosques, calligraphy, and others. One of the mosques that have been built since the time of Walisongo is the Great Mosque of Sang Cipta Rasa, Cirebon. Therefore, the author formulates some problems. First, how is the architectural construction of art? Second, how is its philosophy in terms of the architecture and ornamentation in a mosque? Third, how are types of calligraphy which belong to mosques in the archipelago? To answer these questions, the author uses historical and semiotic approach. The research is a literature study. The method used in this article is analysis-descriptive. The results of this article explained that ornamentation is the development of a sense of beauty that develops abstract patterns taken from processing natural motifs. While calligraphy expresses an abstract understanding of God, so calligraphy is expressed to pour out the power of the revelation of the Qur'an.